Disability Certification - SP, Goswami; S, Venkatesan; S, Mathews (Journal of All India Institute of Speech and Hearing)
Reducing the channels of access provides a chance at catering better services to the stakeholders. A person with disability (PWD) can approach a single professional for his treatment and post treatment care. Allied health care professionals under the Rehabilitation Council of India (RCI) are trained to identify, assess and e ectively treat the temporary or permanent conditions faced by PWD. The authority to issue a certi cate of disability for the bene t of the stakeholders is rightfully theirs in par with medical professionals who base this certi cation on an allied health professionals? report. The idea of streamlined ecient health services will be armed by the certi cation authority endowed on the allied health professional. It will in turn secure the resources of stakeholders in a cost-e ective manner.